Radio Audit: A Visual Podcast Series as The Learning Media to Increase Accounting Students Engagement - Dhika Maha Putri; Ria Zulkha Ermayda; Rizky Firmansyah; Septy Nur Sulistyawati; Siti Mariyah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
Universities are currently focusing on generic skills and students' critical thinking abilities. The demands on the workplace and the transformation in the field of technology cause theoretical knowledge is not enough to be successful in the workplace. As an auditor, students must have expertise, technical training, and professional skills in order to carry out audit implementation and report preparation. Accounting educators make a variety of innovations in response to the need to transfer knowledge in today's online learning environment, one of which is the use of video as a learning tool. The purpose of this study is to investigate the effect of using video podcasts (Radio Audit) on accounting students' engagement in auditing courses. Through a case study approach, this study found that the use of video podcasts increased student engagement in the third dimension (behavioral, emotional, and cognitive). According to the findings of surveys and interviews with students, the use of video podcasts increases student motivation in studying, increases flexibility, and makes it easier for them to understand the main points that must be mastered so that they can be successful in completing the final exam. This research contributes to the field of education by demonstrating that learning by using video podcasts can be an effective means and expands the study of the use of video podcasts in learning in universities.